2017
DOI: 10.1371/journal.pone.0178715
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to disseminating brief CBT for voices from a lived experience and clinician perspective

Abstract: Access to psychological therapies continues to be poor for people experiencing psychosis. To address this problem, researchers are developing brief interventions that address the specific symptoms associated with psychosis, i.e., hearing voices. As part of the development work for a brief Cognitive Behaviour Therapy (CBT) intervention for voices we collected qualitative data from people who hear voices (study 1) and clinicians (study 2) on the potential barriers and facilitators to implementation and engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…Overall, participants referred to the lack of provision of CBTp in their teams, which confirms reports from a recent systematic review regarding the low rates of CBTp implementation (Ince et al ., ). Similar to previous studies (Hazell, Strauss, Cavanagh, & Hayward, ; Prytys et al ., ), our findings indicate the difficulties that clinicians face when implementing CBTp, which include the severity of symptoms and reported lack of insight of people with psychosis. In addition, challenges with consistent attendance increased the pessimistic attitudes of professionals regarding the feasibility of recovery and reinforced the lack of implementation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, participants referred to the lack of provision of CBTp in their teams, which confirms reports from a recent systematic review regarding the low rates of CBTp implementation (Ince et al ., ). Similar to previous studies (Hazell, Strauss, Cavanagh, & Hayward, ; Prytys et al ., ), our findings indicate the difficulties that clinicians face when implementing CBTp, which include the severity of symptoms and reported lack of insight of people with psychosis. In addition, challenges with consistent attendance increased the pessimistic attitudes of professionals regarding the feasibility of recovery and reinforced the lack of implementation.…”
Section: Discussionsupporting
confidence: 92%
“…According to Hazell, Strauss, Cavanagh, et al . (), professionals’ lack of belief in the efficacy of CBTp reinforces commissioners’ lack of investment in CBTp. Similarly, the lack of Coherence in this study might have reinforced the service level barriers which reflected the lack of Collective Action .…”
Section: Discussionmentioning
confidence: 98%
“…During the development of GiVE we found that mental health clinicians were concerned that patients lacked sufficient motivation to engage in self-help (Hazell et al, 2017b). However, the findings from this study offer a different perspective and suggest that people distressed by hearing voices can engage with self-help materials when guidance is offered.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, the voice content itself can act to prevent disclosure (i.e., voices telling the patient not to say anything) ( Beavan and Read, 2010 ). Most often, people do not disclose their voice hearing experiences because of concerns about stigmatizing responses from family, friends, and the wider society ( Beavan et al, 2011 ; Mawson et al, 2011 ; Hazell et al, 2017b ; Bogen-Johnston et al, 2017 ). Even within mental health services, patients are concerned about the potential for stigma from clinicians ( Beavan et al, 2011 ), and the fear of stigma is likely to be reinforced by clinicians who feel it is inappropriate to encourage and initiate conversations about hearing voices ( Coffey and Hewitt, 2008 ).…”
Section: Does a Symptom-specific Approach Generate Additional Barriermentioning
confidence: 99%